A study of Knowledge, Attitude and Behaviour on the Use of Natural Medicine for Type 2 Diabetes Mellitus in Pharmacies in Kendal Regency Area - Santi Setiani; Maria Caecilia N.Setiawati; Yosef Wijoyo (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Diabetes mellitus (DM) is one of the global health challenges that continues to rise, including in Indonesia. However, the lack of education and counseling from pharmacists regarding the use of natural ingredients medicines has the potential to affect the effectiveness of treatment and the management of DM. This study aims to measure the level of knowledge, attitudes, and behaviour of DM patients, related to the use of natural ingredient drugs in DM management. This study uses a cross-sectional method design, starting with the collection of quantitative data. Sampling was conducted using purposive sampling technique over a period of four months. The research involved 101 DM patients from 15 pharmacies in Kendal Regency. The level of knowledge (44.6%), attitude (66.3%), and behaviour (39.6%) of patients in the moderate category. However, the limited knowledge of pharmacists remains a barrier to optimizing pharmaceutical services related to educating patients about natural ingredient medications.